Fatigue‐creep interaction performance of Incoloy 825 nickel‐based superalloy at 650 °C. Issue 6 (16th June 2021) - Huo, X.; Li, F.; Zhu, Q.; Chen, L.; Wang, B.
Abstract: The fatigue‐creep interaction performance of Incoloy 825 nickel‐based superalloy at 650 °C was investigated through introducing the tensile, compressive, and tensile‐compressive strain hold time at the controlled total strain amplitude Δ ϵ t = 0.3 %∼0.7 %. The results show that the Incoloy 825 nickel‐based superalloy exhibits the cyclic hardening behavior, the cyclic hardening behavior followed by cyclic softening behavior and the cyclic hardening behavior followed by cyclic stability during the cyclic deformation with tensile strain hold time, while the alloy exhibits the cyclic hardening behavior and the cyclic hardening behavior followed by the cyclic stability during the cyclic deformation with compressive and tensile‐compressive strain hold time. The relationship between both plastic and elastic strain amplitudes with reversals to failure for the alloy shows a single slope linear behavior, which can be described by the Coffin‐Manson and Basquin equations, respectively. The deformation mechanism of the alloy under three loading condition of fatigue‐creep interaction is mainly the planar slip. In addition, under three loading condition of fatigue‐creep interaction, the cracks initiate and propagate in the transgranular mode. Abstract : The cyclic waveforms for the fatigue‐creep interaction, including the cyclic deformation with tensile, compressive, and tensile‐compressive strain hold time are presented. The hold period was introduced at the maximum tensile strain, compression strain and tensile‐compressive strain, and the corresponding time for each hold period are 5 seconds.